Tick Waste Application in Houses With Warning of Microcontroller Assistant Social Media.: Tick Waste Application in Houses With Warning of Microcontroller Assistant Social Media. - Ritzkal Ritzkal (Institute of Computer Science (IOCS), 2020)
Throwing garbage in its place might be something that is easy for everyone but in fact there are still lots of garbage scattered in any place. This is due to a lack of awareness of the community about the importance of maintaining cleanliness and health of the surrounding environment. Waste is a serious threat to the community, because littering can cause environmental pollution. Sometimes when garbage is dumped at home, sometimes there is no knowledge of the capacity of the garbage can. The impact of the ignorance of the capacity of the garbage can, there will be a buildup of garbage for days that have not been able to be disposed of in the trash. Trash can is a place to temporarily collect garbage, which is usually made of metal or plastic. The objectives of this study are to obtain the physical form of smart dry trash cans to be applied at home and to obtain information on the existence of garbage can capacities with WhatsApp social media and to provide information on the weight of garbage. the research methods used are hardware and software. Assembly for the acquisition of a Smart Trash Assisted by a Microcontroller, namely. Hardware Design through Functional Block Diagram of System Series, Microcontroller Circuit and Network Design, Programming of Microcontrollers with Arduino IDE. Warning on Social Media by WhatsApp. Sensor Testing and Delivery of the Social Media alert system by WhatsApp in 2 ways, namely: Sensor and Loadcell Testing, Testing Delivery of social media editing systems by WhatsApp.